Organtransplantation und Menschenwürde = Organtransplantation and human dignity - Bardenheuer, Hubert J.; Kupatt, Christian; Anselm, Reiner (Der Anaesthesist, 1994)
Modern medicine has succeeded in achieving enormous technical developments. One recent highlight has been the introduction of postmortem organ transplantation. At the same time, serious objections have been raised concerning the radical changes in the cultural conception of the inviolable body. One major objection arises from the conflict of considering a brain-dead person as dead. The presence of brain death is a prerequisite for post-mortem organ donation, because only during this phase of dying does the individual quality as dead while the organs, other than the brain, remain viable. The objection implies scepticism as to the physician's ability to distinguish a dead from a living person. On the other hand, even the critics must rely on the physician's ability to discriminate, e.g., when to discontinue resuscitation. The medical community has not found reasons to restrict the definition of irreversible coma 25 years after its first formulation. It must be clearly recognised that reasons other than medical ones can be decisive for refusing organ donation. One ethical problem is the therapeutic benefit of organ transplantation. The beneficiary of the treatment is not the donor, but another person, the recipient. The concept of human dignity does not allow the use of a person fur purposes other than the ones he/she consents to, as Immanuel Kant stated. Although the human corpse is not a person in the full sense, even if it is protected by the thought of respect for the former person, the life-interest of the organ recipient had to be considered legitimate. The resulting conflict between the respect for the donor and the life-interest of the recipient should be balanced by seeking the donor's consent as far as possible. The proposed information model seems adequate at the moment. A common report of both churches in Germany in 1990 supported postmortem organ transplantation. The report dealt with the medical problems and harmonized them with the Christian value of solidarity. The ethical alternatives to organ transplantation, however, are not mentioned. Within this limitation, the report seems to adequately express the aim to strengthen individual competence and plead for fair perception of the neighbour's life-interest.
Gesehen am 14.11.2023